Chitosan Natural Polymer Material for Improving Antibacterial Properties of Textiles - Li, Jianhui; Tian, Xiao; Hua, Tao; Fu, Jimin; Koo, Mingkin; Chan, Wingming; Poon, Tszyin (ACS applied bio materials, 2021)
In recent years, the textile industry has been seeking to develop innovative products. It is a good choice to organically combine materials with superior functional characteristics and commercial textiles to form products with excellent performance. In particular, textiles made of biological functional materials are often beneficial to human health, which is an interesting research direction. As a biopolymer material, chitosan has the advantages of strong availability, low cost, excellent safety, outstanding performance, etc., particularly the antibacterial property, and has broad application prospects in the textile field. This review provides an overview of the latest literature and summarizes recent innovations and state-of-the-art technologies that can add value to textiles. To this end, preparation of chitosan fiber, synthesis of chitosan nanofiber, antibacterial activity of chitosan fiber, antibacterial activity of chitosan nanofiber, etc., will be discussed. Furthermore, the challenges and prospects of chitosan-based materials used in textiles are evaluated. Importantly, this review can not only help researchers understand the development status of antibacterial textiles, but also help researchers discover and solve problems in this field through comparative reading.